PEMBELAJARAN SEJARAH PADA PROGRAM KEJAR PAKET C - Windarsari, Ranulin; Sunardi, Sunardi; Djono, Djono (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2018)
This study is aimed to describe the implementation of learning history in kejar paket C programs. This study uses the descriptive qualitative method. Data were collected by interviews, documentation, and observation. Data analysis technique use qualitative analysis inductive models with purposive sampling technique. The results of this study are: first, planning learning history in kejar paket C program started from In House Training for educators in kejar paket C program which practiced in the preparation of the learning device are appropriate to the curriculum; second, the implementation of learning history in kejar paket C program involves three patterns of learning consisting of 20% face-to-face interaction, 30% tutorials, and 50% independent activity; third, constraints in the implementation of history learning in kejar paket C program is the readiness of learners in receiving learning materials, learning infrastructure, and the competence of educators in conveying the teaching of history; fourth, evaluation of learning history in kejar paket C program is equal to the formal school.